DEVELOPMENT OF A METHODOLOGY FOR ENHANCING STUDENTS' COMMUNICATIVE CULTURE BASED ON A DIFFERENTIATED APPROACH - Yusupova Gulrukh Nabiyevna (Bright Mind Publishing, 2025)
In today's era of globalization, students studying in higher educational institutions must possess not only professional knowledge but also a communicative culture. Especially in the process of learning English, the formation of these skills based on an individual approach is relevant. From this point of view, the development of students' communicative culture based on a differentiated approach is an important scientific and pedagogical issue. The paper discusses principles, theoretical backgrounds, and practical guidelines on utilizing differentiated approaches to enhance students’ communicative culture.
Keywords: Personality-oriented approach, individual characteristics, culturally relevant pedagogy, ongoing assessment, interactive platforms, teaching strategies.